Urban geography - Kaplan, David H.; Holloway, Steven R. (New Jersey John Wiley & Sons< Inc., 2024)
Urban Geography is an established textbook for undergraduate students with strong sales record. In August 2021 the authors approached us with the idea of updating the title, and a new edition survey was run to explore its potential. All instructors that were contacted endorsed publication, expressing their interest in an updated and expanded version of the textbook.